UV–Visible photo sensing properties of CdS-porous silicon (PS): P-Si and ZnO-PS: p-Si heterostructures metal-semiconductor-metal (MSM) based devices. (2021) - Sarmah, S.; Das, M.; Sarkar, D.
Abstract: Present work reports fabrication of metal-semiconductor-metal (MSM) [1] devices based on CdS-PS: p-Si and ZnO-PS: p-Si heterostructures for photo sensing applications. Field Emission Scanning Electron Microscope (FESEM) analyses confirm growth of hierarchical flower like nanostructured CdS and spherical shaped nanostructured ZnO layers of uniform thicknesses ∼170 and 160 nm respectively on PS: p-Si substrate. UV–visible absorbance spectra for CdS and ZnO nanostructures provide optical band gap of 2.6 and 3.3 eV respectively. Photoluminescence (PL) spectra analyses of the heterostructures show near band edge (NBE) emissions of nanostructured CdS at ∼450–482 nm for CdS-PS: p-Si and at ∼378–398 nm of nanostructured ZnO for ZnO-PS: p-Si along with characteristic PL peaks of PS at ∼600 nm [2] and some trap/defect assisted luminescence bands. Dark current analyses of the heterostructures give values of ideality factors (n) of 3.4 and 4.4 respectively. Heterostructures under increasing illumination intensity (17–71 µW cm −2, 400 nm) show almost symmetric rectification enhancement for positive and negative bias condition with maximum photo to dark current ratio (Iph /Id ) of 10.3 and 34.3 respectively at −2 V bias. ZnO-PS: p-Si heterostructure shows superiority for UV–Visible photo sensing application in terms of high responsivity ∼2.6 AW −1, high EQE ∼800% and response time of ∼1.12 sec compared to ∼0.6 AW −1, 180% and 0.16 sec of CdS-PS: p-Si respectively at biasing of −2 V.